The Role of the Internal Audit Function in Enhancing Risk Management: A Field Study at the National Well Drilling Company (Journal of Economic Additions, 2025)
This Study aims to analyze the impact of using internal auditing as a tool for risk management at the National Well Drilling (ENTP) in hassi messoud ouargla,in the applied part, The researchers relied, in the applied part, on content analysis of official internal audit documents and reports of the company, while employing the descriptive method to examine the theoretical framework. The study’s findings revealed a positive relationship between the quality of the company's internal audit performance and the effectiveness of risk management. Internal auditing contributed to improving risk response and reducing its impact through control recommendationsKeywords:Internal Auditing, Internal Control, Risks, Risk Management, ENTP CompanyJel Classification Codes: M42.G32.D81
Keywords: :Internal Auditing, Internal Control, Risks, Risk Management, ENTP Company